Magnetostructural and magnetocaloric properties of bulk LaCrO3 system. (5th February 2015) - Tiwari, Brajesh; Dixit, A; Naik, R; Lawes, G; Rao, M S Ramachandra
Abstract: We studied magnetic properties of bulk LaCrO3 ; a GdFeO3 -type distorted perovskite, with a predominant antiferromagnetic phase transition at ∼290 K. The bulk LaCrO3 exhibits intrinsic weak ferromagnetism at room temperature, which may arise due to the tilting of CrO6 octahedra, resulting in a non-zero net magnetic moment, as confirmed from the magnetization measurements. A broad magnetically-induced entropy change (− Δ S) is observed with the maxima at 290 K, close to room temperature in LaCrO3 system.